Green synthesis of isopropyl myristate in novel single phase medium Part II: Packed bed reactor (PBR) studies - Rajeshkumar N. Vadgama; Annamma A. Odaneth; Arvind M. Lali (Biotechnology Reports, 2015)
Isopropyl myristate is a useful functional molecule responding to the requirements of numerous fields of application in cosmetic, pharmaceutical and food industry. In the present work, lipase-catalyzed production of isopropyl myristate by esterification of myristic acid with isopropyl alcohol (molar ratio of 1:15) in the homogenous reaction medium was performed on a bench-scale packed bed reactors, in order to obtain suitable reaction performance data for upscaling. An immobilized lipase B from Candida antartica was used as the biocatalyst based on our previous study. The process intensification resulted in a clean and green synthesis process comprising a series of packed bed reactors of immobilized enzyme and water dehydrant. In addition, use of the single phase reaction system facilitates efficient recovery of the product with no effluent generated and recyclability of unreacted substrates. The single phase reaction system coupled with a continuous operating bioreactor ensures a stable operational life for the enzyme.